The nature of vertical hydrogeochemical zoning of petroleum deposits (exemplified by the Nadym-Taz interfluve, West Siberia); Geology and Geophysics; Vol. 45, Issue 8 - Shvartsev S. L. Stepan Lvovich (2004, 2004)
В фонде НТБ ТПУ отсутствует